Transplantation of Gut Microbiota From High-Fat-Diet-Tolerant Cynomolgus Monkeys Alleviates Hyperlipidemia and Hepatic Steatosis in Rats - Gao, Jiang-Mei; Rao, Jun-Hua; Wei, Zhi-Yuan; Xia, Shou-Yue; Huang, Li; Tang, Ming-Tian; Hide, Geoff; Zheng, Ting-Ting; Li, Jia-Huan; Zhao, Guo-An; Sun, Yun-Xiao; Chen, Jian-Huan (Frontiers in Microbiology, 2022)
Emerging evidence has been reported to support the involvement of the gut microbiota in the host’s blood lipid and hyperlipidemia (HLP). However, there remains unexplained variation in the host’s blood lipid phenotype. Herein a nonhuman primate HLP model was established in cynomolgus monkeys fed a high-fat diet (HFD) for 19 months. At month 19%, 60% (3/5) of the HFD monkeys developed HLP, but surprisingly 40% of them (2/5) exhibited strong tolerance to the HFD (HFD-T) with their blood lipid profiles returning to normal levels. Metagenomic analysis was used to investigate the compositional changes in the gut microbiota in these monkeys. Furthermore, the relative abundance of Megasphaera remarkably increased and became the dominant gut microbe in HFD-T monkeys. A validation experiment showed that transplantation of fecal microbiota from HFD-T monkeys reduced the blood lipid levels and hepatic steatosis in HLP rats. Furthermore, the relative abundance of Megasphaera significantly increased in rats receiving transplantation, confirming the successful colonization of the microbe in the host and its correlation with the change of the host’s blood lipid profiles. Our results thus suggested a potentially pivotal lipid-lowering role of Megasphaera in the gut microbiota, which could contribute to the variation in the host’s blood lipid phenotype.